Investigating theattitudes of special educated physical education prospective teachers towards disabled people - Emrah Aykora; Sinan Uğraş (Physical Education of Students, 2020)
Purpose: It’s aimed in this study to investigate the attitudes of physical education prospective teachers who had special education lessons towards disabled ones.